2010
DOI: 10.1149/1.3372570
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Study on Chemical Bonding States of High-k Gate Stacks for Advanced CMOS

Abstract: The paper reviews the non-destructive depth profiling of the composition and the chemical structure of high-κ/Si using angleresolved photoelectron spectroscopy. Analyses of Si 2s spectra show that the reactivity between ScOx or CeOx and Si substrate is lower than that between LaOx and Si substrate. Analyses of Ce 3d 5/2 and O 1s spectra show that a oxidation state of Ce changes from Ce 4+ to Ce 3+ by PDA in N 2 at and above 400°C and changes from Ce 3+ to Ce 4+ by PDA in O 2 at 300°C. This implies that a oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…On the other hand, the increase in the number of La-O-Si bonds with the thickness of the W film indicates that silicate reaction could be controlled by changing the thickness of the W film. 23,24) The windows of the hysteresis in the C-V curves for TiN (40 nm)/W (6 or 12 nm)/ La 2 O 3 (3.5 nm)/n-Si and W (60 nm)/La 2 O 3 (3.5 nm)/n-Si gate stack capacitors annealed for 2 s are summarized in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the increase in the number of La-O-Si bonds with the thickness of the W film indicates that silicate reaction could be controlled by changing the thickness of the W film. 23,24) The windows of the hysteresis in the C-V curves for TiN (40 nm)/W (6 or 12 nm)/ La 2 O 3 (3.5 nm)/n-Si and W (60 nm)/La 2 O 3 (3.5 nm)/n-Si gate stack capacitors annealed for 2 s are summarized in Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
“…[5] To overcome the scaling restriction of microelectronic device size, Si-based conventional dielectric materials such as SiO 2 need to be replaced with advanced high permittivity (high-k) materials. [6][7][8][9] Various high-k materials, such as barium strontium titanate (BaSrTiO 3 ), titanium oxide (TiO 2 ), zirconium oxide (ZrO 2 ), aluminum oxide (Al 2 O 3 ), tantalum oxide (Ta 2 O 5 ), hafnium oxide (HfO 2 ), and silicon nitride (Si 3 N 4 ) are being investigated to meet the requirement. [10][11][12][13][14][15][16] Among these metal oxides, Ta 2 O 5 is the most promising gate insulator and an appropriate candidate for memory dielectrics in storage capacitors in place of SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve an EOT of 0.5 nm, which is the ultimate specification reported in ITRS roadmap, high-k should be in directly contact with Si substrate without any SiO 2 based interfacial layer. It has been reported that rare earth oxides can achieve a direct contact structure by forming silicates at Si interface [3] and an EOT of 0.5 nm has already been demonstrated [4]. In this paper, we will focus on the interface properties of La-silicate/Si interface through fabrication of MOS capacitors on Si wafers with different orientations.…”
Section: Introductionmentioning
confidence: 99%